Vibrational frequencies of clusters: arsenic oxide, carbon nitride, copper oxide, selenium and related compounds with different atoms / Ahmad Nazrul bin Rosli. - Rosli, Ahmad Nazrul (2012)
The density functional theory (DFT) has been used to solve the SchrÄodinger equation. The computer programmes have been developed which give a real advantage for solving large matrices in DFT that seem impossible to write by hand. The Amsterdam density functional (ADF) and DMol3 of Accelerys have been used to calculate the vibrational frequencies of the atoms and molecules. The clusters of the molecules have been made for the study of glasses such as AgGeSe, AsSe, AsS, AsO, CuO, Se, FeP, FeAs, CN and graphene. These calculations are in good agreement with the experimental results. The local density approximation (LDA) and the generalized gradient approximation(GGA) both are used for solving eigen values of the SchrÄodinger equation. The double numerical and double numerical with polarized orbitals as a basis set for the wave functions are used in these calculations. The calculated frequencies have been compared with the experimentally measured Raman spectra to identify the clusters which are present in the material. This calculation is in accord with the experimentally observed Raman spectra.